Caracterização dos quimiorreceptores de O2 envolvidos no controle dos reflexos cardio-respiratórios de trairão, Hoplias lacerdae (Teleostei, Erythrinidae) em resposta à hipóxia ambiental - Micheli, Mariana Andrade de (Universidade Federal de São Carlos, 2008)
The ability to sense and respond to oxygen availability in the environment is of extreme functional importance for fish. This is even more so in tropical freshwater habitats where environmental hypoxia can occur rapidly in space and time. Recent physiological studies on the cardio-respiratory response of tropical fishes have focused on hypoxia tolerant species. This aim of this study was to examine the neural control and function of the cardio-respiratory system in a fish that is adapted to living at high levels of oxygen. Trairão, Hoplias lacerdae was chosen because it is a member of the Erythrinidae family, in which most of species are hypoxia tolerant, including some where the O2 receptors has already been characterized. The study focused on investigation of the localization, distribution and orientation of chemoreceptors of O2 in trairão. Also how the cardio-respiratory parameters were modified by hypoxia. The fish were submitted to selective denervations of the branchial branches of the cranial nerves IX and X. These were, (1) only IX nerve sectioned at the 1st gill arch (IX; n = 9), (2) first gill arch both IX and branch of X sectioned (G1; n = 9), (3) all four gill arches both IX and X sectioned (G4; n = 8), (4) a control group (n = 8) and (5) a sham-operated group that underwent surgery but no nerves were sectioned (n = 4). A cannula was inserted into the ventral aorta to monitor changes in heart rate and blood pressure. Ventilation rate and amplitude was also monitored with a cannula through the roof of the buccal cavity. The fish were exposed to a gradual hypoxia from 140 to 10 mmHg. Either the internal and external surfaces of the gill were treated with NaCN to determine the receptors orientation. Results showed that the receptors related to the heart rate control and ventilation amplitude were distributed over all gill arches on both the internal and external surfaces, and the branches of the both nerves IX and X were involved in these responses. This pattern differs from that observed for the ventilation rat. The receptors involved in the control of this response are located internally to the first gill arch. Tairão also showed blood pressure control chemorecptors on the first gill arch, involved in a very efficient barostatic control. Extrabranchial O2 chemoreceptors were not identified in trairão. This differs from the hypoxia tolerant fish, where extrabranchial chemoreceptors are important to start the cardio-respiratory responses the most fast and accurate possible
Keywords: Fisiologia comparada; Quimiorreceptores; Erythrinidae; Função cardio-respiratória; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA DE ORGAOS E SISTEMAS::FISIOLOGIA DA RESPIRACAO